ON THE FUNDAMENTAL CONTRADICTIONS OF FORMATION PERSONALITIES IN MODERN CONDITIONS OF GLOBALIZATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the process of globalization, which is characterized by extreme inconsistency, and in the conditions of the information society, a new type of personality is being formed, which in many respects differs from all previous types. The article identifies and philosophically analyzes the fundamental contradictions of the formation of a modern personality type. The real person is be- ing replaced and slowly, persistently replaced by the virtual one, which minimizes relationships and communication with people who are physical in relation to him, begins to consider and evaluate them mainly from a functional point of view. There is a massive erasure of the ethnic or national form of personality, when relatively small peoples cannot seriously resist the pressure of cultures belonging to more technologically successful peoples. One of the main contradictions of the globalization pro- cess is that it simultaneously brings benefits and something opposite to them. For several decades now, humanity has entered a new phase of its development – the information society, with the rapid growth of human potential, with artificial intelligence.
Keywords: personality, globalization, information society, virtual reality, virtual personality type.